2011
DOI: 10.1007/s10578-011-0233-6
|View full text |Cite
|
Sign up to set email alerts
|

Familial Risk Factors for the Development of Somatoform Symptoms and Disorders in Children and Adolescents: A Systematic Review

Abstract: The aim of this study was to examine whether familial risk factors for the development of somatoform symptoms and somatoform disorders in children and adolescents can be deduced from studies which investigated the intergenerational transmission of functional abdominal pain and somatoform disorders. A systematic review of articles published in English and German since 1990 was performed. Twenty-three relevant studies were found. The following putative familial risk factors for the development of somatoform symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
1
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 52 publications
3
51
1
6
Order By: Relevance
“…Similarly, mothers may report more child somatic symptoms than fathers [36], and parental somatization can lead to the development of somatization in children [37]. The PHQ-15 potentially provides a useful measure of somatic symptoms in perinatal samples based on the current findings with postpartum women.…”
Section: Discussionmentioning
confidence: 85%
“…Similarly, mothers may report more child somatic symptoms than fathers [36], and parental somatization can lead to the development of somatization in children [37]. The PHQ-15 potentially provides a useful measure of somatic symptoms in perinatal samples based on the current findings with postpartum women.…”
Section: Discussionmentioning
confidence: 85%
“…Results of different studies indicate that parents of children with functional somatic symptoms often experience psychosocial problems, psychiatric disorders as well as somatoform symptoms and/or somatic diseases themselves (22). Kılıçaslan et al (14) reported that mothers of children having FC diagnosis had significantly higher level of psychological complaints.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is well documented that patients with ED and SFD have higher rates of health care use across multiple health care settings compared with the general population 5,9 and that psychological factors, such as denial, poor motivation, alexithymia (ie, difficulty identifying and verbally expressing feelings), and limited insight affect their health care use, [10][11][12][13] it is not known if they use services with the same rates and patterns. Furthermore, although other similarities can be gleaned from separate studies of patients with ED and patients with SFD (eg, female preponderance, 6,14 age of presentation in adolescence, 4,6 increased risk of ED and SFD in the offspring of parents with anxiety and depressive disorders 15,16 ), it remains unclear how much biopsychosocial characteristics overlap between these 2 patient groups. As such, the current study aims to describe the demographic and clinical characteristics and health care use of medically admitted children, adolescents, and young adults with ED and SFD at a tertiary teaching pediatric facility.…”
mentioning
confidence: 99%